Ubiquitous Intelligence and Computing 7th International Conference, UIC 2010, Xi$1 (Ban, China, October 26-29, 2010. Proceedings /s - Yu, Zhiwen; Liscano, Ramiro; Chen, Guanling; Zhang, Daqing; Zhou, Xingshe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 7th International Conference on Ubiquitous Intelligence and Computing, UIC 2010, held in Xi$1 (Ban, China, during October 26-29, 2010. The 36 papers presented in this volume, together with the three keynote speeches, one invited paper, 6 special session papers, and 5 PSC special track papers, were carefully reviewed and selected from 128 submissions. The topics covered are activity, localization, and user identification; ubiquitous services and applications; sensor networks; infrastructure, middleware and context-awareness; distributed systems and services; wireless and mobile ad hoc networks; ubiquitous intelligence and services; and pervasive social computing.s
Keynote Speeches -- Programming Pervasive Spaces -- Ubiquitous Experience Media -- The Operating System for the Computer of the 21st Century -- Invited Paper -- Extracting Social and Community Intelligence from Digital Footprints: An Emerging Research Area -- Activity, Localization, and User Identification -- Smart Itinerary Recommendation Based on User-Generated GPS Trajectories -- Inferring User Search Intention Based on Situation Analysis of the Physical World -- GPS Calibrated Ad-Hoc Localization for Geosocial Networking -- Ontology-Enabled Activity Learning and Model Evolution in Smart Homes -- Support Vector Machines for Inhabitant Identification in Smart Houses -- Towards Non-intrusive Sleep Pattern Recognition in Elder Assistive Environment -- Ubiquitous Services and Applications -- The Making of a Dataset for Smart Spaces -- to the Business Processes with Ambient Media - Challenges for Ubiquitous and Pervasive Systems -- A Steerable Tangible Interface and Its Evaluation -- Alerting Accidents with Ambiguity: A Tangible Tabletop Application for Safe and Independent Chemistry Experiments -- Dependency Relation Based Detection of Lexicalized User Goals -- Identification of Gait Patterns Related to Health Problems of Elderly -- Sensor Networks -- An Energy Efficient Localization Strategy for Outdoor Objects Based on Intelligent Light-Intensity Sampling -- RESS: A Data Dissemination Protocol Using Residual Energy and Signal Strength for Wireless Sensor Networks -- Design and Implementation of Mobile Sink Node in SDMA Applications -- RCO: A Multi-channel MAC Protocol with Random Cooperation for Sensor Networks -- Power and Bandwidth Efficiency of IEEE 802.15.4 Wireless Sensor Networks -- Protecting Source Location Privacy in Wireless Sensor Networks with Data Aggregation -- Infrastructure, Middleware and Context-Awareness -- A Middleware for Intelligent Environments and the Internet of Things -- An Infrastructure for Real Objects Augmentation with Additional Personalized Information Services -- A Low-Cost Ubiquitous Family Healthcare Framework -- A Lattice-Theoretic Approach to Runtime Property Detection for Pervasive Context -- Modeling Files with Context Streams -- CASPER: Mining Personalized Services -- Distributed Systems and Services -- A Simple Public-Goods Game Based Incentive Mechanism for Resource Provision in P2P Networks -- A Novel Framework for Service Description and Operations -- A Self-Adaptive Hardware/Software System Architecture for Ubiquitous Computing Applications -- Toward Distributed Declarative Control of Networked Cyber-Physical Systems -- AdContRep: A Privacy Enhanced Reputation System for MANET Content Services -- Context-Awareness Handoff Planning in Heterogeneous Wireless Networks -- Wireless and Mobile Ad hoc Networks -- On the Improving Strategies upon the Route Cache of DSR in MANETs -- LALO: A Link-Aware Lightweight Routing Protocol for Data Delivery in Vehicular Ad Hoc Networks -- POCOSIM: A Power Control and Scheduling Scheme in Multi-Rate Wireless Mesh Networks -- Modeling Contacts and Mobility for Wireless Mobile Networks -- A Method to Improve Adaptability of the Minstrel MAC Rate Control Algorithm -- A New Location-Aware Hierarchical Routing Protocol for MANETs -- Special Session: Ubiquitous Intelligence and Services -- Towards an Efficient and Accurate EEG Data Analysis in EEG-Based Individual Identification -- Activity Recognition on an Accelerometer Embedded Mobile Phone with Varying Positions and Orientations -- A Hybrid Content Delivery Approach for a Mixed Reality Web Service Platform -- Analyzing the Behavioral Structure Characteristics from Web Traffic -- A Smartphone-Based Obstacle Sensor for the Visually Impaired -- SSP: Smart Service Provider A Smart Environment Providing Contextual Services on Android Mobile Devices -- Special Track: Pervasive Social Computing -- Using Cohesive Subgroups for Analyzing the Evolution of the Friend View Mobile Social Network -- Towards Topic-Based Trust in Social Networks -- Mlogger: An Automatic Blogging System by Mobile Sensing User Behaviors -- Managing Workplace Resources in Office Environments through Ephemeral Social Networks -- Contextual Biometric-Based Authentication for Ubiquitous Services.
Keywords: Computer science; Computer Communication Networks; Artificial intelligence; Biometrics; Social sciences -- Data processing; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Computers and Society; Computer Appl. in Social and Behavioral Sciences; Personal Computing; Biometrics